Implementasi Kebijakan Rencana Tata Ruang dan Wilayah dan Desa Tangguh Bencana di Nusa Tenggara Barat - Khansa Nur Fathiya; Pujo Widodo; I Dewa Ketut Kerta Widana; Herlina Risma Juni Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
West Nusa Tenggara is located on active fault line along the Lombok and Sumbawa Faults, which often causes high magnitude earthquakes and can cause major impact on society, environment and infrastructure. The purpose of this study is to determine the implementation of spatial and regional planning policies in earthquake risk reduction in West Nusa Tenggara. The method used in this research is descriptive qualitative research using purposive sampling technique and literature study. The informant of this research is the Planning Analyst of the Regional Planning and Development Agency of West Nusa Tenggara. The result of this research is that disaster risk management strategies are implemented collaboratively between agencies from various sectors. In the pre-disaster stage, the local government ensures the readiness of the region and the community against the potential threat of natural disasters, by forming disaster resilient villages. Spatial and regional plan policies in West Nusa Tenggara are directed at natural disaster mitigation and adaptation to reduce disaster risk.